Engineering RNA polymerase to construct biotechnological host strains of cyanobacteria - Turunen, Otso (Wiley-Blackwell, 2025)
Application of cyanobacteria for bioproduction, bioremediation and biotransformation is being increasingly explored. Photoautotrophs are carbon-negative by default, offering a direct pathway to reducing emissions in production systems. More robust and versatile host strains are needed for constructing production strains that would function as efficient and carbon-neutral cyanofactories. We have tested if the engineering of sigma factors, regulatory units of the bacterial RNA polymerase, could be used to generate better host strains of the model cyanobacterium Synechocystis sp. PCC 6803. Overexpressing the stress-responsive sigB gene under the strong psbA2 promoter (SigB-oe) led to improved tolerance against heat, oxidative stress and toxic end-products. By targeting transcription initiation in the SigB-oe strain, we could simultaneously activate a wide spectrum of cellular protective mechanisms, including carotenoids, the HspA heat shock protein, and highly activated non-photochemical quenching. Yellow fluorescent protein was used to test the capacity of the SigB-oe strain to produce heterologous proteins. In standard conditions, the SigB-oe strain reached a similar production as the control strain, but when cultures were challenged with oxidative stress, the production capacity of SigB-oe surpassed the control strain. We also tested the production of growth-rate-controlled host strains via manipulation of RNA polymerase, but post-transcriptional regulation prevented excessive overexpression of the primary sigma factor SigA, and overproduction of the growth-restricting SigC factor was lethal. Thus, more research is needed before cyanobacteria growth can be manipulated by engineering RNA polymerase.